The Effect of Spoiler Shape and Setting Angle on Racing Cars Aerodynamic Performance - Eftekhari, Hesam; Al-Obaidi, Abdulkareem Sh. Mahdi; Eftekhari, Shahrooz (Universitas Pendidikan Indonesia, 2020)
Automotive racing is one of the favorite sports of human being. There have been many developments in past decades by car engineers to improve the performance of the engine and increase the aerodynamic efficiency of the race cars to achieve a better lap time and get a better placement safely. One of the ways to improve the aerodynamic performance of a race car is to use rear spoilers. This study by using ANSYS FLUENT numerically investigated the effect of the spoiler shape and setting angle on the aerodynamic characteristics of a race car and then it was validated by conducting wind tunnel experiment. Lift and drag coefficient of NACA0012, NACA4412, and S1223 are determined in Reynoldâ€™s number of 2Ã—105 as an airfoil and as spoiler on ERC model which is a conceptual car model inspired by Porsche 911. It was found that ERC model with spoiler would have better aerodynamic efficiency compared to ERC model without spoiler. Also, S1223 at -6 degrees was identified as the optimized configuration as it generates the highest downforce. Even though the drag coefficient at this setting angle is slightly higher, but in terms of stability and handling IT is at its best. Overall, this study would help car manufacturers, for racing and commercial purposes, to have a better insight into the effect of spoiler configuration on the aerodynamic performance of cars. Hence, the stability, handling, and efficiency of the cars can be further improved by selecting the suitable spoiler configuration.